Methoden zur technologieorientierten Programmierung für die 3D-Lasermikrobearbeitung - Pursche, Lars (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)
The advantages of three-dimensional Laser Micro Processing are only accessible through computer aided planning of the manufacturing steps. Therefore, methods have been developed which reduce the planning time and increase the flexibility of the manufacturing and thus allow a greater workpiece variet